Β‐LAPachone ameliorates doxorubicin‐induced cardiotoxicity via regulating autophagy and Nrf2 signalling pathways in mice. Issue 4 (27th November 2019) - Nazari Soltan Ahmad, Saeed; Sanajou, Davoud; Kalantary‐Charvadeh, Ashkan; Hosseini, Vahid; Roshangar, Leila; Khojastehfard, Mehran; Haiaty, Sanya; Mesgari‐Abbasi, Mehran
Abstract: β‐LAPachone (B‐LAP) is a naphthoquinone that possesses antioxidant properties. In the present investigation, the protective effect of B‐LAP against doxorubicin (DOX)‐induced cardiotoxicity was examined in mice. Thirty‐five mice were divided into 5 groups: control group, B‐LAP (5 mg/kg) group, DOX (15 mg/kg) group, DOX+B‐LAP (2.5 mg/kg) group and DOX+B‐LAP (5 mg/kg) group. B‐LAP was administered orally for 14 days of experimental period. A single dose of DOX (15 mg/kg) was injected intraperitoneally on day 3. Cardiac function, histoarchitecture, indices of oxidative stress and circulating markers of cardiac injury were examined. B‐LAP (5 mg/kg) decreased serum levels of lactate dehydrogenase (LDH), creatine kinase MB (CK‐MB) and cardiac troponin I (cTnI), and ameliorated cardiac histopathological alterations. In addition to increasing cellular NAD + /NADH ratio, B‐LAP up‐regulated the cardiac levels of SIRT1, beclin‐1, p‐LKB1 and p‐AMPK, and reduced the cardiac levels of p‐mTOR, interleukin (IL)‐1β, TNF (tumour necrosis factor)‐α and caspase‐3. B‐LAP also elevated the nuclear accumulation of Nrf2 and simultaneously up‐regulated the protein levels of haem oxygenase (HO‐1) and glutathione S‐transferase (GST) in the hearts of DOX mice. While B‐LAP reduced malondialdehyde concentrations in heart of DOX‐treated mice, it further promoted the activities of cardiac superoxide dismutase (SOD), glutathione peroxidase (GPX) and catalase (CAT).In accordance with increased cell survival, B‐LAP significantly improved the cardiac function of DOX mice. Collectively, these findings underline the protective potential of B‐LAP against DOX‐induced cardiotoxicity by regulating autophagy and AMPK/Nrf2 signalling pathway in mice.